Accelerating the solar-thermal energy storage via inner-light supplying with optical waveguide - Yafang Zhang; Jiebin Tang; Jialin Chen; Yuhai Zhang; Xiangxiang Chen; Meng Ding; Weijia Zhou; Xijin Xu; Hong Liu; Guobin Xue (Nature Communications, 2023)
Abstract Solar-thermal storage with phase-change material (PCM) plays an important role in solar energy utilization. However, most PCMs own low thermal conductivity which restricts the thermal charging rate in bulk samples and leads to low solar-thermal conversion efficiency. Here, we propose to regulate the solar-thermal conversion interface in spatial dimension by transmitting the sunlight into the paraffin-graphene composite with side-glowing optical waveguide fiber. This inner-light-supply mode avoids the overheating surface of the PCM, accelerates the charging rate by 123% than that of the traditional surface irradiation mode and increases the solar thermal efficiency to ~94.85%. Additionally, the large-scale device with inner-light-supply mode works efficiently outdoors, indicating the potential of this heat localization strategy in practical application.